Schriftmässige Beantwortung der Frage: Was von dem weltüblichen Tanzen und Spielen zu halten sey und ob es nicht mit zur Christlichen Freyheit gehöre?: als ein Anhang zu den Betrachtungen von der Freyheit der Gläubigen vom Gesetz - Bogatzky, Carl Heinrich von (Wäysenhaus, 1750)
This manual is an early German example of the literature against the practice of dancing. In this case, Bogatzky (1690-1774) compares gambling with dancing, and asks the reader to consider these practices in the context of Scripture, especially the Ten Commandments